Research on Field‐Assisted Gallium Nitride Nanorod Array Photocathode. Issue 1 (29th August 2022) - Liu, Lei; Zhangyang, Xingyue; Lu, Feifei; Tian, Jian
Abstract : To improve the electron collection efficiency of gallium nitride (GaN) nanorod array photocathode, external electric field is used to assist collect photoelectrons and a theoretical model of field‐assisted photoelectric emission for GaN nanorod array is established herein. The results indicate that inclined incident light can improve the photoelectron collection efficiency on the side surface of the nanorod and that external electric field can promote the drifting of the photoelectron to the top surface of the nanorod. The square array with a filling fraction of 0.7 reaches its maximum photoelectron collection efficiency at the incident angle of 5° and field intensity of 0.1 V μm −1 . This paper might play a theoretical guiding role in the fabrication of photodetectors with high photoelectric conversion efficiency. Abstract : External electric field is used to assist collect photoelectrons, and a theoretical model of field‐assisted photoelectric emission for GaN nanorod array photocathode is established. COMSOL Multiphysics and MATLAB are used for simulation experiments of the GaN photocathode. High‐photoelectric conversion efficiency square‐arranged GaN nanorod array is designed with inclined incident light and electric field.